TROLI MAKANAN MENGGUNAKAN MOTOR DC 50W/12V SEBAGAI PENGGERAK TAMBAHAN - Sepdian (LPPM Politeknik Jambi, 2021)
motor 50 W / 12 V DC as an additional driver for the food trolley which previously used human power, to overcome this this study aims to facilitate work that previously used human power assisted by a 50 W/12V DC motor. to drive a 50 W / 12 V DC motor, a voltage in the range of 11V-12V is needed on a 50 W/4.16A power supply whose source comes from a dry battery, with a power of 25 Kg with a plate capacity of 12 - 16 plates of food with a capacity of 1500 grams/plate power 21 Ah battery with a maximum usage time of 60 minutes, the design and process of making a trolley, especially the use of a DC Motor as an additional driver for a food trolley. The process of making a machined trolley unit includes stages, namely: observation, design, manufacture, trolley assembly and testing. This trolley has a load capacity of 25 kilograms while the empty weight of the trolley is 34.5 kilograms and has a Dc Motor with a 390 series with a voltage of 12 Volts, a power of 50 Watts and a current use of 3-5 Amperes and the source used comes from a dry battery.